How do you integrate #int x^2e^(4x)# by integration by parts method?

Answer 1

There is a faster method

Introduce #t# and write #I = int e^(4tx) dx# Now differentiate with respect to t #(dI)/dt = int 4x e^(4tx) dx# Once more #(d^2I)/dt^2 = int 16x^2 e^(4tx) dx# #I = e^(4tx)/(4t)# #(dI)/dt= x/te^(4tx) - e^(4tx)/(4t^2)# and again #(d^2 I)/(dt^2) = ( 4x^2/t -x/(t^2)-x/t^2 + 2/t^3 1/4)e^(4tx)# #(d^2I)/dt^2 = (4x^2-2x + 2)e^(4x)# Our integral is 1/16 I #J= I/16 = (x^2 - x/4 + 1/8)e^(4x)#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

The answer is #=e^(4x)(x^2/4-x/8+1/32)+C#

Integration by parts is

#intuv'dx=uv-intu'vdx#

Here, we have

#u=x^2#, #=>#, #u'=2x#
#v'=e^(4x)#, #=>#, #v=e^(4x)/4#

Therefore,

#intx^2e^(4x)dx=(x^2e^(4x))/4-int2x*e^(4x)dx/4#
#=(x^2e^(4x))/4-1/2intx*e^(4x)dx#
We apply the integration by parts a second time to find #intx*e^(4x)dx#
#u=x#, #=>#, #u'=1#
#v'=e^(4x)#, #=>#, #v=e^(4x)/4#

Therefore,

#intx*e^(4x)dx=x/4e^(4x)-inte^(4x)dx/4#
#=x/4e^(4x)-e^(4x)/16#

Putting the results together,

#intx^2e^(4x)dx=(x^2e^(4x))/4-1/2(x/4e^(4x)-e^(4x)/16)#
#=e^(4x)(x^2/4-x/8+1/32)+C#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 3

To integrate ( \int x^2e^{4x} ) by integration by parts, use the formula:

[ \int u , dv = uv - \int v , du ]

Choose ( u = x^2 ) and ( dv = e^{4x} , dx ).

Then, find ( du ) and ( v ).

[ du = 2x , dx ] [ v = \frac{1}{4}e^{4x} ]

Now, apply the integration by parts formula:

[ \int x^2e^{4x} , dx = \frac{1}{4}x^2e^{4x} - \frac{1}{2} \int xe^{4x} , dx ]

Now, integrate ( \int xe^{4x} ) using integration by parts again:

Choose ( u = x ) and ( dv = e^{4x} , dx ).

Find ( du ) and ( v ).

[ du = dx ] [ v = \frac{1}{4}e^{4x} ]

Apply the integration by parts formula again:

[ \int xe^{4x} , dx = \frac{1}{4}xe^{4x} - \frac{1}{4} \int e^{4x} , dx ]

Integrate ( \int e^{4x} , dx ) to get ( \frac{1}{16}e^{4x} ).

Now, substitute the values back into the original integral:

[ \int x^2e^{4x} , dx = \frac{1}{4}x^2e^{4x} - \frac{1}{2} \left( \frac{1}{4}xe^{4x} - \frac{1}{16}e^{4x} \right) ]

[ = \frac{1}{4}x^2e^{4x} - \frac{1}{8}xe^{4x} + \frac{1}{32}e^{4x} + C ]

Where ( C ) is the constant of integration.

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7